Preparation of liposomal doxorubicin-graphene nanosheet and evaluation of its in vitro anti-cancer effects. (3rd April 2019) - Tajvar, Samira; Mohammadi, Soheila; Askari, Alireza; Janfaza, Sajjad; Nikkhah, Maryam; Tamjid, Elnaz; Hosseinkhani, Saman
Abstract: In recent years there has been much interest in development of multifunctional drug delivery systems. In this work, liposomes that contain doxorubicin (Dox), a potent anticancer drug, and graphene nanosheets (GNS) were prepared. The GNSs have excellent optical properties, such as photoluminescence which enables tracking of the liposomes, high absorption in ultra violet region of electromagnetic spectrum which can be exploited in photodynamic and photothermal therapy, and low toxicity to mammalian cells. Nanoliposomes were prepared using the thin film hydration method. Dox and GNSs were loaded to the liposomes during the hydration of the lipid film. Liposomes were characterized and the profile of in vitro drug release, cellular uptake, and cytotoxicity of the prepared liposomes on MCF-7 cells were determined. Despite the earlier reports, the liposomes have kept their spherical structures in the presence of GNSs. The cytotoxicity of liposomal Dox and GNSs were shown to be higher than the free forms of them. Novel nanoliposomes that contain GNSs have provided a multi-functional system with the potential of tracking, photodynamic and photothermal therapy. Further improvements of this versatile nanosystem would be promising for treatment of cancer.